Using mobile technology to facilitate the user experience of group holiday decision-making - Zhang, Lanyun (2018)
With the increasing expenditure of international tourism around the world, the topic of studying group holiday decision-makings has drawn attentions in the fields of tourism research and business management (Mottiar & Quinn, 2004; Wang et al., 2004; Carr, 2005; Jacobsen & Munar, 2012; Assayer et al., 2011). Yet, the user experience of tourists in groups has been reported to be in need of improvements (Garcia et al., 2009). For example, such user experience lacks effective information sharing among group members, a convenient communication environment, and an efficient decision-making support (Decrop, 2005). A possible solution is technology, such as smart phones, that this technology has evolved from single-purpose communication devices into dynamic tools that support users in a wide variety of tasks (Böhmer et al., 2011). This thesis is devoted to studying the user experience related to technology-supported group holiday decision-making. It aims to investigate how mobile technology can help a group of people to make holiday decisions with a view to enhance the user experience. This thesis reviews theoretical approaches to help understand the concepts and related works (Chapter 2). Research methods are also discussed, including the framework of user-centred design employed in this research, and the challenges of exploring user experience in this context (Chapter 3). This thesis investigates the user experience of how tourist groups plan their trips, including an understanding of user behaviour and requirements. It proposes a model of group trip planning process to describe the core elements of group holiday planning (Chapter 4). Then, it explores a number of factors that influence the group holiday planning process (Chapter 5). Next, tourism information presentation is examined in terms of exploring the characteristics of different types of textual tourism information on the Internet and how the perceptions of tourists are affected by these different types of information accordingly (Chapter 6). Design implications are derived and discussed to guide the design of technology, for the purposes of facilitating group holiday planning process. Chapter 7 describes the three key elements considered in this design of mobile technology: usability, personalisation, and enjoyable user experience. The development of a prototype of this technology, #GT-Planner, is also elaborated (Chapter 7). Finally, this thesis investigates the user experience of this prototype (#GT-Planner), in which both subjective approaches (i.e., questionnaires and interviews) and objective approach (i.e., physiological measurement) are employed (Chapter 8). #GT-Planner is shown to facilitate the group holiday decision-making process and result in an enriched user experience. The thesis primarily discusses the understandings of the user experience of group holiday decision-making, the design implications for group holiday decision-making, the framework of user-centred design, and methods for examining the users in a group and evaluating the technology. Finally, findings and conclusions are specified and highlighted, along with a discussion of the contributions derived from this thesis and the avenues for future work.